Taxonomy and Modelling the Distribution and Ecology of the Genus Glenea (Subfamily Lamiinae, Coleoptera: Cerambycidae) in Sarawak - NGUMBANG, JUAT (UNIMAS, 2025)
The longhorn beetle is one of the most significant wood-boring insects from the family Cerambycidae. Yet, Sarawak has little enthusiasm for research into this family's biology, ecology, or taxonomy. As a result, little is known about this family. Aside from its broad contribution to scientific knowledge, understanding species taxonomy, composition, distribution, and abundance is essential for pest management, conservation, and species monitoring. The secondary and hill mixed dipterocarp forests of Sungai Sekabai, Sebauh, Bintulu; Ulu Sungai Mujuk, Julau; Loagan Bunut National Park, Lanjak Entimau Wildlife Sanctuary, Batang Ai National Park, and Ulu Baram were the survey locations of the Cerambycidae. Most of the Cerambycidae species in these woodlands were collected using the butterfly net, Malaise traps, and handpicking. Depending on the accessibility in these forests from 2004 to December 2006, a random survey was undertaken. A total of 406 individuals from 59 different species of Glenea were assessed from the museum collection. The specimens studied were from the Sarawak Forestry Corporation, Kuching, the Unimas Insect Reference Collection, Universiti Malaysia Sarawak, and the Sarawak Museum Collection, Kuching (S. M. Coll). (Forest Research Centre Coll.). Out of the 59 species that were reviewed, 18 new species nomen nudum have been described. The Glenea species of Sarawak are split into 6 major clades, with the smallest clade consisting of 3 species and the largest clade consisting of 23 species, based on dendogram reconstruction utilizing species morphological features distances analysis in R. The differentiation of the biological and sampling processes results in a more process-driven estimate of diversity, and hierarchical multispecies models that incorporate both the detection process and the occurrence state, such as the Multiple Species Occupancy Model (MSOM), offer a promising direction for the future. The local community (all species present at one site), the entire metacommunity, and these potent community models can all represent patterns, such as covariate connections (regional pool of species in the wider area of study). As a result of its ability to make inferences at all levels of a meta-community (species, community, and metacommunity), as well as its explicit handling of measurement error, the Community N-Mixture Model, which is based on the abundance of a community of species, meets our main criteria for a flexible and reliable community modelling framework. This includes the estimation of species richness at various scales. This study is intended to be a foundational resource for references in the future, a comprehensive checklist, and a contribution to our knowledge of this genus.